2016
DOI: 10.1021/acs.langmuir.6b02824
|View full text |Cite
|
Sign up to set email alerts
|

Particle Zeta Potentials Remain Finite in Saturated Salt Solutions

Abstract: The zeta potential of a particle characterizes its motion in an electric field and is often thought to be negligible at high ionic strength (several moles per liter) due to thinning of the electrical double layer (EDL). Here, we describe zeta potential measurements on polystyrene latex (PSL) particles at monovalent salt concentrations up to saturation (∼5 M NaCl) using electrophoresis in sinusoidal electric fields and high-speed video microscopy. Our measurements reveal that the zeta potential remains finite a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 43 publications
(76 reference statements)
5
17
0
Order By: Relevance
“…The fit of the solid curve to the experimental data are quite good for C > 0.1 M, which is remarkable because the Gouy-Chapman equation used to derive [7] assumes a thermodynamically ideal solution; this is unlikely to be valid for such large concentrations of NaCl. A similar conclusion was reached by Garg et al (45).…”
Section: Resultssupporting
confidence: 87%
“…The fit of the solid curve to the experimental data are quite good for C > 0.1 M, which is remarkable because the Gouy-Chapman equation used to derive [7] assumes a thermodynamically ideal solution; this is unlikely to be valid for such large concentrations of NaCl. A similar conclusion was reached by Garg et al (45).…”
Section: Resultssupporting
confidence: 87%
“…It shows that the zeta-potential increases with the increasing Na + concentration to about − 9 mV in the tested range. This is in consistent with the phenomenon that the zeta-potential of colloid at high salt concentration as a finite value 2 . The increase of zeta-potential in Na + solution is mainly due to the suppression of the double electric layer as the increase of ionic strength in the solution.…”
Section: Resultssupporting
confidence: 90%
“…As the surface charge is hard to be determined directly, zeta potential measurements are most commonly applied to quantify the electrostatic properties of carbonate rock surfaces and oil droplets in solutions. The quantitative changes in the magnitude of surface charge can result in correspondent changes in the zeta potentials 2 , 3 . It was reported that the zeta-potential of carbonate minerals was reported to show different trend from the clastic minerals in low salinity brines 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Saturated zeta potential measurements have been reported using an ultrasound technique 40 but in prohibitively large volumes for valuable manufactured or field-collected samples. Imaging velocimetry under a microscope has been reported 41 but this technique measures small numbers of micron-scaled particles yielding a statistically poor sample from the parent population and missing the nano-scale completely. Further still, in order to detect the residual electrophoretic mobility in high molarities from which zeta potential is calculated and which, as we report in this work, tend to be rather low in magnitude, a potential difference across the cell must be applied for periods long enough that the images of the particles explore a region of the detector plane larger than the Rayleigh resolution of the imaging microscope.…”
mentioning
confidence: 99%